Framework for assessing serviceability and socio-economic risk associated with PPPs projects in Libya - Marzouk, Mohammed; El-Hesnawi, Mahmoud (Journal of Civil Engineering and Management, 2018)
On a global scale, limited financing for the development and operation of infrastructure projects has pushed authorities to encourage private investors to enter public-private partnerships (PPPs). In this respect, procurement of infrastructure projects such as bridges, water plants, airports, and roads has been adopted through PPPs. This has also applied to the oil-rich country of Libya which experienced severe economic and political problems in the past decade. This paper presents a systematic framework for risk assessment and appraisal of PPPs infrastructure projects. This framework is capable of identifying probable adverse effects that represent key influential factors on the private sector in a socio-economic environment and related to key performance indicators (KPIs) in order to assess the operational efficiency in developing and financing infrastructure projects. This framework proposes a new integrated system that comprises of the following: fault tree, artificial neural networks, and analytical network process. The aim of this system is to ensure sustainable availability of finances that are considered essential for the development of PPPs infrastructure projects in Libya. considering different alternative funding models, it suggests a means of auditing PPPs structure to carry out improved performance for PPPs projects in Libya.